Lateral impact response of the concrete filled steel tube columns with and without CFRP strengthening. (1st June 2016) - Shakir, A.S.; Guan, Z.W.; Jones, S.W.
Highlights: The influence of concrete types on the impact resistance of the tube columns. Normal concrete and recycled aggregate concrete. The effect of impactor configurations on the impact response of the tube columns. The local CFRP reinforcement on the reduction of the peak force. Abstract: This paper presents a study on the dynamic response of normal or recycled aggregate concrete filled steel tube (NACFST and RACFST) columns subjected to lateral projectile impact and the effect of the Carbon Fibre Reinforced Polymer (CFRP) jacketing on the structural behaviour of those columns. Eighty four specimens were studied to investigate the influence of the tube length, configuration of the impactor, concrete type and local reinforcement on the dynamic response. The results indicate that both the RACFST and NACFST specimens have a similar deformation shape, and the impact resistance of the RACFST specimens is comparable to that of the NACFST. The results also show that the additional confinement of the CFRP reduces the global displacement for both the RACFST and NACFST specimens. In addition the concrete filling increases the maximum impact force by 217%, 182% and 157% respectively for the short, medium and long tubes. On the top of the extensive experimental work, theoretical approaches were proposed to predict the maximum load and the corresponding displacement for all the columns tested, providing reasonably good correlation with the experimental results. Using the analytical model developed, further studies were undertaken to investigate the effects of the tube geometry, material properties, impactor configuration and impact energy on the structural response of the concrete filled tube columns.